The Important of Strategic thinking in Insurance companies: Applied Research in Iraqi Insurance Companies (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Increasing the interest in Strategic features and its productivity about Insurance policies for their important role for companies in general and insurance company for specific, therefore, this research aims to stand on the business of insurances companies,their departments and branches in strategic features and their impact in the productivity at Insurance Policies and attracting the attention of Strategic leaders at the administration of the company for the importance of research variables, this research aims to measuring the impact of Strategic features on competitive advantages in increasing the productivity of employees of insurances policies, at time many countries rely heavily on services in their economies and to achieve the research goal by made a search schema that ensures the future variable. dependent variable and sub variables, relying on schema changing , three hypotheses formulated and to test the hypotheses validation it had been selected a sample from the top administration and departments managers to represents the search community , the sample which includes (18) member like Members of Board Directorsand department managers at National Insurances companies and the information about search samples was collected by using a questionnaire form and a set of annual reports; data were processed by using a set of description and statistical methods to study the relationship between search variables.